Prospects of Community Participation in the Management of Shasha Forest Reserve, Osun State, Nigeria (2002)
Forests are located mostly in the rural communities and they contribute substantially to poverty alleviation in such communities. Thus sustainability of Forest Resources is of utmost importance in rural economy. It is therefore being realized globally that for any forestry programme to succeed, it must involve the local communities. In Nigeria, efforts at involving the people in forest management have not been very successful because they did not really address the needs and interests of the people. It is important to know what exactly the people want and the best role they can play in forest management in order to achieve success. This paper therefore investigated the perception of the communities living around Shaslm Forest Reserve concerning community forestry and their potential roles m such arrangement. Stratified random, sampling was used to select eight of the forty communities within and around the forest reserve. A total of eighty-two questionnaires were administered on three categories of the stakeholders viz: hunters (32); Harvesters/fishermen (40) and forestry official (10). Results indicated that 71% of the respondents are favorably disposed to the idea of community participation m the management of the Forest reserve. Also, community members showed- interest in forest protection, commercial seedlings production, maintenance and harvesting operations. There was no evidence of bitter relationship among the stakeholders. A method of benefit sharing was also proposed.